Corporate Governance and Financial Performance toward Sustainability Reporting: A Moderation Study of Firm Size in IDX Companies - Tuzzohra, Fatimah; Satria, Hendy; Pardede, Ranat Mulia; Marlinda, Charly; Sahara, ⁠Masyitah As (Indonesian Scientific Publication, 2025)
This research explores the influence of good corporate governance and financial performance on sustainability report disclosures, with company size considered as a moderating factor. The study targets mining companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. The governance indicators analyzed include the presence of a board of directors, audit committees, and independent commissioners. By utilizing secondary data and a purposive sampling method, a total of 20 mining firms were selected for evaluation. The findings demonstrate that both the board of directors and profitability significantly and positively contribute to the level of sustainability disclosures. In contrast, the audit committee and independent commissioners do not exhibit a notable impact. Furthermore, company size is found to strengthen the relationship between the board of directors and profitability with sustainability reporting, although it does not have a moderating effect on the roles of the audit committee and independent commissioners.